REVIEW: DEVELOPMENT OF NATURAL MATERIALS AS BREAST CANCER ANTICANCER - Kaniawati, Marita; Cintiya Dewi , Silvy; Azzah Wulandari, Yulinda; Dimas Alamanda, Vidiana (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to review various efforts in developing anticancer therapies based on medicinal plants and synthetic compounds, particularly for breast cancer, which has high prevalence and mortality rates. Method: Data were collected through a literature review of scientific journals published between 2010 and 2020. The study analyzed the potential of various medicinal plants and bioactive compounds using both experimental and computational approaches.  Results: The review revealed that medicinal plants such as soursop leaves, galangal, moringa leaves, Kasumba Turate flowers, and red dragon fruit peels exhibit significant anticancer potential. Their activities include cytotoxicity, proliferation inhibition, and apoptosis induction in T47D and MCF-7 breast cancer cells. Additionally, an in silico approach was employed to evaluate bioactive compounds like galangin and quercetin, which demonstrated potential interactions with specific molecular targets such as HER-2 and SIRT1. Novelty: This study highlights the importance of exploring both natural and synthetic anticancer compounds to develop more effective and safer therapies. The integration of in silico analysis provides a deeper understanding of molecular interactions, supporting the advancement of targeted breast cancer treatments.